Ethnic networks and US exports - Subhayu Bandyopadhyay; Cletus C. Coughlin; Howard J. Wall (Institute for the Study of Labor (IZA), 2006)
This paper provides new estimates of the effects of ethnic network on U.S. exports. In line with recent research, our dataset is a panel of exports from U.S. states to 29 foreign countries. Our analysis departs from the literature in two ways, both of which show that previous estimates of the ethnic-network elasticity of trade are sensitive to the restrictions imposed on the estimated models. Our first departure is to control for unobserved heterogeneity with properly specified fixed effects, which we can do because our dataset contains a time dimension absent from previous studies. Our second departure is to remove the restriction that the network effect is the same for all ethnicities. We find that ethnic-network effects are much larger than has been estimated previously, although they are important only for a subset of countries.
Keywords: F10; R10; 330; ethnic networks; state exports; Export; Außenhandelselastizität; Gravitationsmodell; USA; Welt; Soziales Netzwerk